Vacuum Condensates as a Mechanism of Spontaneous Supersymmetry Breaking - Antonio Capolupo; Marco Di Mauro (Advances in High Energy Physics)
A possible mechanism for the spontaneous breaking of SUSY, based on the presence of vacuum condensates, is reviewed. Such a mechanism could occur in many physical examples, at both the fundamental and emergent levels, and would be formally analogous to spontaneous SUSY breaking at finite temperature in the TFD formalism, in which case it can be applied as well. A possible experimental setup for detecting such a breaking through measurement of the Anandan-Aharonov invariants associated with vacuum condensates in an optical lattice model is proposed.